Sources of resistance to Curtobacterium flaccumfaciens pv. flaccumfaciens in common bean accessions - Valentini,Giseli (2011)
The purpose of this study was to identify common bean genotypes resistant to bacterial wilt to be used as resistance sources in breeding programs targeting resistant cultivars. A total of 67 accessions, five cultivars and one control were evaluated, which were artificially inoculated with the Curtobacterium flaccumfaciens pv. flaccumfaciens isolate Cff 2634. The results prove the existence of alleles that confer tolerance to bacterial wilt in the cultivars IAC Carioca Aruã, IAC Carioca Pyatã and IAC Carioca Tybatã. The mean grades of disease symptoms were lowest in BAF 122 (Xan 159); this accession was identified as disease-tolerant and indicated for use in breeding programs to develop resistant cultivars.